The volcano daughters - Balibrera, Gina Maria (Pantheon Books, 2024)
"A saucy, searingly original debut about two sisters raised in the shadow of El Salvador's brutal dictator, El Gran Pendejo, and their flight from genocide, which takes them from Hollywood to Paris to cannery row, each followed by a chorus of furies, the ghosts of their murdered friends, who aren't yet done telling their stories. El Salvador, 1923. Graciela grows up on a volcano in a community of indigenous women indentured to coffee plantations owned by the country's wealthiest, until a messenger from the Capital comes to claim her: at nine years old she's been chosen to be an oracle for a rising dictator-a sinister, violent man wedded to the occult. She'll help foresee the future of the country. In the Capital she meets Consuelo, the sister she's never known, stolen away from their home before Graciela was born. The two are a small fortress within the dictator's regime, but they're no match for El Gran Pendejo's cruelty. Years pass and terror rises as the economy flatlines, and Graciela comes to understand the horrific vision that she's unwittingly helped shape just as genocide strikes the community that raised her. She and Consuelo barely escape, each believing the other to be dead. They run, crossing the globe, reinventing their lives, and ultimately reconnecting at the least likely moment. Endlessly surprising, vividly imaginative, bursting with lush life, The Volcano Daughters charts, through the stories of these sisters and the ghosts they carry with them, a new history and mythology of El Salvador, fiercely bringing forth voices that have been calling out for generations"--